Telaah Diksi Agama dalam Kamus Al-Munjid Fi Al-Lughah Wa Al-A'lam - Muhammad Subhan (Universitas KH. A. Wahab Hasbullah Tambakberas Jombang, 2023)
Al-Munjid's dictionary is often used by the majority of Muslims in the world because it is considered easy in vocabulary entry and search. However, there is still much debate about its use because the vocabulary is considered to influence the faith of a Muslim. Some scholars consider al-Munjid's dictionary to have links with the orientalist movement, which carries a hidden agenda toward the Islamic world. So the purpose of this study is to criticize and examine diction related to religious tendencies towards the concept of al-Munjid's dictionary and see the accuracy of the interpretation or meaning given by looking at